Implementasi Metode Waspas Dengan Pembobotan Roc Dalam Penerimaan Peserta Didik Baru - Syahputra, Dedi (Management of Information System Journal, 2024)
− The aim of this research is to implement the WASPAS method with weighting using ROC in the process of accepting new students at S Panglima Polem Rantauprapat Middle School. The WASPAS method is used as a framework for evaluating and ranking prospective students based on a number of relevant criteria. ROC is commonly used in performance analysis in the medical and computer science fields to produce more accurate weightings in the selection process. This research will outline the steps for implementing the WASPAS method with ROC weighting, including data collection, identification of criteria, and weighting calculations. It is hoped that the results of this research can make a significant contribution to improving the process of accepting new students at S Panglima Polem Rantauprapat Middle School, by increasing objectivity, accuracy and transparency in the selection of prospective students. It is hoped that this will help the school in selecting prospective students who best suit the school's needs and improve the quality of education at the school.